Design and development of a wearable health monitoring system for elderly people - Mehad, Shakkharatul Haque; Islam, Showmik; Rahman, Mashfiqur; Khan, Naziur Rahman (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.